Value in Hepatitis C Virus Treatment: A Patient-Centered Cost-Effectiveness Analysis - Mattingly, T. Joseph (Pharmacoeconomics, 2019)
BACKGROUND: Innovations in hepatitis C virus (HCV) therapy included in traditional comparative evaluations focus on sustained virologic response (SVR) without addressing challenges patients report beyond virologic cure. This study aims to evaluate the cost-effectiveness of HCV drug therapy with a patient-centered approach. METHODS: An individual-based Markov model was constructed using guidance from a stakeholder advisory board (SAB), a patient Delphi panel, and published literature to evaluate direct-acting antivirals (DAAs) compared to no treatment. The United States (US) health sector and societal perspectives were considered for 10- and 20-year time horizons. Inputs for treatment costs and effectiveness reflect a generic regimen. Indirect costs used for the societal model included estimates from self-reported productivity in a matched-control sample. Beyond the traditional quality-adjusted life-year (QALY) health outcome, this study included two novel measures developed from the Delphi panel and SAB: infected life-years and workdays missed. All costs were measured in 2018 US dollars. RESULTS: Health sector costs and QALYs were higher in the treatment group in both 10- and 20-year models. Total infected life-years and workdays missed were reduced in the treatment group for both models. When costs of absenteeism, presenteeism, and patient/caregiver time were included, the DAA intervention was cost-saving at both 10 and 20 years. Health sector results were sensitive to drug costs and utility estimates for post-SVR health states. Societal results were sensitive to presenteeism estimates and drug costs. CONCLUSION: Treatment was cost-effective from a health sector perspective and cost-saving when including non-health costs such as patient/caregiver time and productivity. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40273-019-00864-8) contains supplementary material, which is available to authorized users.